Significance of p53‐binding protein 1 (53BP1) expression in thyroid papillary microcarcinoma: association with BRAFV600E mutation status. Issue 5 (5th September 2013) - Mussazhanova, Zhanna; Matsuda, Katsuya; Naruke, Yuki; Mitsutake, Norisato; Stanojevic, Boban; Rougounovitch, Tatiana; Saenko, Vladimir; Suzuki, Keiji; Nishihara, Eijyun; Hirokawa, Mitsuyoshi; Ito, Masahiro; Nakashima, Masahiro
<x xml:space="preserve">Abstract</x> Aims In a previous report, we proposed that analysis of 53BP1 expression by immunofluorescence could be a useful tool in estimating the level of genomic instability (GIN), as well as the malignant potential, of thyroid tumours. In an attempt to clarify the value of 53BP1 expression as a new molecular marker for the aggressiveness of thyroid papillary microcarcinoma (PMC), we assessed the association between the type of 53BP1 expression and clinicopathological features such as tumour size, extrathyroidal invasion, lymph node metastasis and BRAFV600E mutation of PMC. Methods and results A total of 36 surgically resected thyroid tumours, including 13 PMC and 23 conventional papillary thyroid carcinomas (PTC), were available for this study. Analysis using immunofluorescence revealed that the incidence of an abnormal or high DNA damage response (DDR) type of 53BP1 expression was significantly higher in PTC than PMC. BRAFV600E mutation was not associated significantly with tumour aggressiveness in either PMC or PTC cases. Abnormal/high DDR type of 53BP1 expression was associated closely with both BRAFV600E mutation and papillary and/or trabecular architecture of PMC. Conclusions Abnormal/high DDR type of 53BP1 expression might be associated with GIN and papillary/trabecular morphology at an early stage of PTC carcinogenesis through BRAFV600E mutation.